Upaya Meningkatkan Kompetensi bagi Pustakawan Sekolah Dasar Anggota Atpusi Pamekasan melalui Pengabdian Kepada Masyarakat : Pelatihan dengan Aplikasi SLIMS - Shintawati, Yanuastrid Shintawati (Institut Agama Islam Negeri Salatiga, 2023)
The development of information technology-based services that are currently carried out by school library managers must of course be balanced with the skills of managers in the field of using information technology devices and the ability to manage management in school libraries. These skills are very much needed considering that managing an organization such as a library requires a high focus and being able to innovate the services that are managed so that the dissemination of information products can be carried out optimally. Departing from the problems experienced by many school librarians, the initiative to conduct community service emerged with the main idea of school library management at various school levels. Community service is carried out to assist school library managers in understanding the process or workflow of school library management appropriately, while also providing understanding and skills in terms of service development, use of library information systems and other developments regarding the use of library information systems that can be used. optimally in the process of disseminating library information. The target of community service is the manager of the school library in general and members of the Pamekasan ATPUSI in particular for those who do not have a library educational background. This community service activity is carried out within a month divided into 4 sessions or parts with each session driven by lecturers whose knowledge is linear with the material presented. The PKM participants are more than 50 people, most of whom are school librarians, and a small number are university librarians. PKM activities went well from start to finish, participants also received rewards in the form of electronic certificates containing the amount of training time that the participants had undergone which was certainly useful as a support for their performance.